From “protection” and “preservation” to “development” and “right”: Anew approach of objective of shariah via waqf mua-qqat - Mohamad, Nor Asiah; Laeba, Muhammad; Hamdan, Omar (The Islamia University Of Bahawalpur, IUB, Pakistan, 2021)
This paper analyses the main objectives of Shariah and its application in waqf. Having acknowledged the priority of the objectives, this paper seeks to expand the scope of the objective with justification to facilitate the ijtihadibasis in ensuring sustainability of waqf. It is argued that a new dimension of protection and preservation of mal as the objective of Shariah is necessary in rel-evantisation of waqflocally and globally. This paperadopts a doctrinal analysis based the primary and secondary sources of Shariah and the Malaysian laws. Itstudies the new dimension of protec-tion and preservation in the perspective of the importance of human development and property rights of waqf practices in Malaysia with special reference toWaqf Muaqqat. The findings show that the employment of ijtihadand fatwawould serve to make waqf stable, flexible and sustainable in developing the legal framework for Waqf Muaqqatin Malaysia